The vegetarian ethics and the spirit of capitalism - Redzić, Saduša F. (Sociološki pregled, 2018)
The text explains the main elements of the ethics of a life, spiritual and moral commitment: vegetarianism. It provides an initial insight into its attitude towards the “spirit of capitalism”. By means of the analytical-descriptive method, the author breaks down vegetarian ethics into elements of moral behavior towards animals, planets and nature, future generations, and self. The number of supporters of this life philosophy is growing and they may soon become important social actors on a global scale. Vegetarian ethics, although essentially opposed to some of the important elements of capitalism, that is, to those relating to massive rearing and the use of animals in industry, poses no danger to the system itself. Moreover, the vegetarian industry is rapidly developing, as well as its market, becoming a contemporary global phenomenon.
Keywords: activism; industry; capitalism; vegetarianism; ethics